Rethinking poverty and development policy in the Caribbean in the age of globalization. - RAMPHALL, Davin (1994)
Argues that the existing paradigms of Caribbean development are flawed and development programmes marked by ecological degradation. Advances the concept of political ecology to account for the nature and causes of poverty. Suggests a rethinking of the poverty issue in the region, and the type of development policy which will address the concerns of the region's poor.